Analisis Penggunaan Light Fishing pada Gillnet Sebagai Upaya Meningkatkan Hasil Tangkapan Ikan Di Desa Danar Kabupaten Maluku Tenggara - Erwin Tanjaya; Fatmawati Marasabessy; Nabila C. Marasabessy (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2026)
This study aims to determine the species composition of gillnet catches, both with and without the use of a light fishing aid; to prove that the use of light fishing on gillnets increases the catch weight; and to determine the net position relative to the light source that produces the highest catch weight. The type of light fishing used in this study for gillnet fishing was an underwater submersible lamp (LACUBA). This research employed the Experimental Fishing method, with four setting operation conducted, while hauling and sorting were carried out after a soaking time of approximately ± 8 hours. The results showed that the fish caught during gillnet operations were divided into two groups: the Main Catch (HTU) and Bycatch (HTS). The HTU group consisted of 2 species of large pelagic fish with a total weight of 169,653 kg. The HTS group consisted of 5 species with a total weight of 59,466 kg. Statistical analysis proved that catches obtained using nets with lights (JDL) were heavier than those obtained using nets without lights (JTL), meaning that the use of light fishing on gillnets significantly increased the catch weight. Statistical testing also demonstrated a significant difference in catch results based on the net position relative to the light source. Fish catches from JDL during the study were distributed across all net panels. The non-parametric Kruskal–Wallis test showed that the distance between the light and the net affected gillnet catches, with an asymp. sig value of 0.002 ≤ 0.05.